2021
DOI: 10.3389/fimmu.2021.735913
|View full text |Cite
|
Sign up to set email alerts
|

Follicular Helper T (TFH) Cell Targeting by TLR8 Signaling For Improving HBsAg-Specific B Cell Response In Chronic Hepatitis B Patients

Abstract: Identifying signaling pathways that induce B cell response can aid functional cure strategies for chronic hepatitis B infection (CHB). TLR8 activation with ssRNA was shown to enhance follicular helper T cell (TFH) function leading to improved B cell responses in vitro. We investigated whether this mechanism can rescue an exhausted immune response in CHB infection. Effect of TLR8 agonism on supporting cytokines and TFH and B cells were evaluated using ex vivo and in vitro assays. The ability of an oral TLR8 ago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 40 publications
(76 reference statements)
2
19
0
Order By: Relevance
“…The phenotypic and functional differences between HBsAg and hepatitis B core antigen (HBcAg) specific B cells in a same patient suggest that high levels of HBsAg may lead to programming obstacles of HBsAg specific B cells through continuous stimulation. Follicular helper T cell can improving HBsAg-specific B cell response in chronic hepatitis B patients targeting by TLR8 signaling ( 40 ).…”
Section: Hbsag Is Related To Hbv Specific Immune Dysfunctionmentioning
confidence: 99%
“…The phenotypic and functional differences between HBsAg and hepatitis B core antigen (HBcAg) specific B cells in a same patient suggest that high levels of HBsAg may lead to programming obstacles of HBsAg specific B cells through continuous stimulation. Follicular helper T cell can improving HBsAg-specific B cell response in chronic hepatitis B patients targeting by TLR8 signaling ( 40 ).…”
Section: Hbsag Is Related To Hbv Specific Immune Dysfunctionmentioning
confidence: 99%
“…At the same time, it has been reported that NK cells in patients with chronic HBV infection can mediate immune tolerance or immune injury [ 93 ]. Other studies have shown that HBsAg can interfere with toll-like receptors (TLRs) in the monocyte/macrophage signaling pathway to inhibit the release of cytokines, which may help to establish a chronic infection [ 94 , 95 ]. However, Kim et al [ 86 ] have shown that there is no significant difference in the composition of immune cells between monocytes and NK cells in the serum low-level HBsAg group and serum high-level HBsAg group.…”
Section: Formation Mechanism Of Persistent Low-level Hbsag Expressionmentioning
confidence: 99%
“…To investigate immunophenotyping by flow cytometry [8], PBMCs from BL and 8 h post-selgantolimod treatment were thawed, and after washing, 0.5-1 × 10 6 cells/panel were labeled with antibodies (flow panels listed in Table S1) at 4 • C for 30 min. After staining, cells were washed twice with FACS buffer (1× PBS/2% FBS), followed by fixation with 2% paraformaldehyde.…”
Section: Flow Cytometry (Facs) and Intracellular Cytokine Staining (Ics)mentioning
confidence: 99%
“…Preclinical and clinical studies have shown that downstream inflammatory immune mediators from TLR8 signaling result in preliminary efficacy for the treatment of cancer and viral infections [7]. Recently, we reported that in CHB patients, TLR8 signaling upregulated the follicular helper T (T FH ) cell functions and rescued the exhausted phenotypes in an IL-12-dependent manner [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation